Multi-Track Dispositions - Vetter, Barbara (Philosophical Quarterly, 2013)
It is a familiar point that many ordinary dispositions are multi-track, that is, not fully and adequately characterisable by a single conditional. In this paper, I argue that both the extent and the implications of this point have been severely underestimated. First, I provide new arguments to show that every disposition whose stimulus condition is a determinable quantity must be infinitely multi-track. Secondly, I argue that this result should incline us to move away from the standard assumption that dispositions are in some way importantly linked to conditionals, as presupposed by the debate about various versions of the ‘conditional analysis’ of dispositions. I introduce an alternative conception of dispositionality, which is motivated by linguistic observations about dispositional adjectives and links dispositions to possibility instead of conditionals. I argue that, because of the multi-track nature of dispositions, the possibility-based conception of dispositions is to be preferred.